Pengujian dan Sistem Kerja Test Bench Hydraulic Pump Gear Type - Abdul Halik; Muhammad Taufik; Hidayat Hidayat; Abdul Halim; Darma Aviva (MEDIA PERSPEKTIF : Journal of Technology, 2021)
Hydraulic system is one of the systems on the heavy equipment unit which is very important for students to understand. The problem that exists in the heavy equipment engineering laboratory at this time is that there is no hydraulic pump test equipment to determine whether the pump that has been repaired is in standard condition or not. To overcome the problems and to support the lecture process, the hydraulic pump test equipment was made. as a tool for testing the feasibility and specifications of the gear type pump. After all the design processes and assembling the required tools, a series of tests will be carried out. The form of tool testing is carried out in the form of pump flow liters per minute, pump pressure in various RPM variations. From the test results, it was found that at RPM 900 the pressure was 100 Psi Flow reading 11 and Flow rate 209, at RPM 1100 pressure 12 Psi Flow reading 15 and Flow Rate 285, At 1372 Pressure 14 Psi Flow reading 19 and flow rate 361, RPM 1500 Pressure 16 Psi Flow reading 19 and Flow rate 437